Socio-economic coordinates and morbidity profile of the inhabitants of a peri-urban area of Srinagar district of Jammu and Kashmir India: a cross sectional study - Ahmad, Javeed; Fazili, Anjum B.; Shah, Rohul J.; Qulsum, Reyana (International Journal Of Community Medicine And Public Health, 2023)
Background: The present study was planned to find out socio-economic coordinates and morbidity profile of the inhabitants of a peri-urban area of Srinagar district- urban field practice area of Sher-i-Kashmir Institute of Medical Sciences (SKIMS). Methods: A cross-sectional community-based house to house study of Anchar area (peri-urban) was conducted for a period of six months. Out of six localities/mohallas of anchar, three localities/mohallas representing the core area and comprising the major chunk of population were purposively selected for the study. All the households of the selected localities were included in the study. Results: The inhabitants of area are moderately positioned on socio-economic scale. The area lacks an adequate liquid waste disposal system. The prevalence of tobacco use was found to be 30.61%. 10.94% of the total population was found to be morbid. Most common morbidities found were hypertension (5.15%) followed by diabetes (1.41%), hypothyroidism (1.23%) and cardiovascular disease (0.82%). Conclusions: Life style diseases are preponderate among the study population. Sustained and regular health check-ups ought to be carried out with a special focus on awareness and education.